Sharia economic law analysis of the stability and liquidity of tether currency investments - Lia Indah Khilmina; Cici Dea Permata Exsti; Bella Mei Mulya Wati (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the interpretation of Islamic economic law regarding Tether Currency investments and its impact on economic productivity and effectiveness in the context of societal progress in the 5.0 era. The development of financial technology (fintech) has introduced various digital assets, including stablecoins such as Tether (USDT), which offer the potential for investment diversification but also raise questions regarding their compliance with Sharia principles. Using a qualitative-descriptive approach and literature review, this study explores fatwas related to digital assets, the characteristics of Tether, and their implications for achieving Sharia issues and objectives (maqasid syariah). The results indicate that the legal status of Tether in the Islamic economy still requires in-depth review, particularly regarding the issues of gharar, riba, and maisir. Although Tether has the potential to increase transaction efficiency and investment accessibility in the 5.0 era, its productivity and effectiveness in driving societal progress depend heavily on compliance with Sharia principles and clear regulations. This study recommends the development of a comprehensive fatwa framework for digital assets to ensure halal and blessed investments for society.